Estrategias metodológicas y su influencia en la comprensión lectora de los estudiantes del cuarto año de la Escuela Básica Leonidas Plaza Guitierrez del recinto la Lucha - Mayorga Pisco, Julieta Beatriz (2018)
The present research work is a descriptive and interpretive study of the influence of the Methodological Strategies on the Reading Comprehension of the fourth grade boys and girls of the Leonidas Plaza Gutiérrez school. To carry out this study, we first identify the strategies applied by Teaching and levels of understanding. The reading of the students, the evaluation of the results of the comprehension strategies. This research is guided by a qualitative approach, the phenomenon is described and interpreted in the study. Techniques and instruments such as observation, interview and test aimed at students were used. The information collected was ordered by instrument and triangulation was made from each report, in this way the results were reached. Among the main findings we can find that the teacher applies reading comprehension strategies such as silent reading, oral reading, exploration through images, comprehension questions, inference of unknown words, among others. Fourth grade students have reached the literal level and the inferential level of reading comprehension. The results of the application of the methodological strategies are verified in the abilities and the levels of the relations that the students of the fourth degree are used, most of them have reached the literal level and the inferential level, but only the minority reaches the critical level Reading. Some of the advantages of their strategies are most of the students.